THEORETICAL AND SCIENTIFIC BASES OF INCREASING THE LIQUIDITY OF COMMERCIAL BANKS IN INVESTMENT ACTIVITIES - Kucharov Jahongir Ovlayarovich (Modern American Journals, 2025)
This article describes the investment activities of commercial banks and its theoretical and scientific foundations, and presents scientific views, proposals and recommendations on the impact of investment activities on economic efficiency.
Keywords: Investment, activity, bank, analysis, risk, credit, forecast, return, attractiveness, efficiency.